Comparative analysis of morphological characteristics in men's and women's artistic gymnastics in the Olympic Games 2016 in Rio de Janeiro, Brazil - Atikovic, A.; Delaš Kalinski, S.; Nozinovic Mujanovic, A.; Kremnicky, J. (Slovak Journal of Sport Science, 2017)
Purpose. Success in sports certainly depends on the morphological characteristics of the athletes, some of which are basic body height and weight, which are evaluated with respect to the current age of athletes. The aim of this study is to determine whether there is a statistically significant difference in the body height and weight between the disciplines of the male and female participants on the Olympic Games 2016 in Rio de Janeiro, Brazil. Basic procedures. The sample included all the Olympic Athletes in Rio de Janeiro 2016, (191 athletes; WAG, n = 97 and MAG, n = 94). The following variables were chosen: body weight (kg), body height (cm). Main findings. The results not showed significant differences between six apparatus in men's artistic gymnastics and four in womens artistic gymnastics in body height and weight. In the Olympic Games 2016, women are on average shorter than men for 12.34 cm and weight less for 14.75 kg. Correlations between body height and weight amounts to (MAG: R=.712; p < 0.01) and (WAG: R=.755; p < 0.01). Conclusions. This research is important in setting comparative parameters in the selection process and sport specialization regarding morphological characteristics according to different events of gymnasts in the elite level.